Exposición de máscaras para socializar la Diablada Pillareña en el contexto patrimonial, a los estudiantes de la carrera de Pedagogía de las Artes y Humanidades de la Universidad Nacional de Chimborazo, en el Museo y Centro Cultural Riobamba - Moya Moreno, Edwin Oswaldo (2024)
The objective of this research work was to develop an artistic exhibition of masks to introduce the Diablada Pillareña, focusing on its heritage value, to students of the Pedagogy of Arts and Humanities degree at the National University of Chimborazo. This approach not only sought to educate students about the festivity, but also to deepen their understanding of masks and their cultural relevance, allowing them to reflect on the impact of these manifestations on society. The theoretical framework included the analysis of key concepts such as masks, artistic exhibitions and cultural heritage, also addressing the sociocultural effect of the Diablada Pillareña and its characters. The methodology applied was mixed, integrating quantitative and qualitative approaches through a survey and an interview, which allowed evaluating the effectiveness of the exhibition as a tool for cultural socialization. The results demonstrated that the artistic exhibition was a successful means of generating interest and awareness around this traditional festivity, showing great acceptance and effectiveness among students. In conclusion, the exhibition was a meaningful experience that fostered greater knowledge and appreciation of the cultural and heritage value of the Diablada Pillareña, strengthening the students' connection with their cultural roots and the preservation of these traditions.